Arterial oxygen saturation during ascending to altitude under various conditions: Lessons from the field - Burtscher, M. (Journal of Science and Medicine in Sport, 2008)
When hypoxia increases during ascending in the mountains, ventilatory control and the related oxygenation may be challenged. The pre-treatment by intermittent hypoxia will elevate ventilation and offset hypoxemia and acetazolamide may inhibit peripheral chemosensitivity and act through central mechanisms. To study these effects in the field, one well-trained male mountaineer performed four ascents from low (1300 m) to higher altitude (2600 m): (1) under control conditions, (2) after intermittent hypoxia, (3) after pre-treatment with acetazolamide, and (4) after intermittent hypoxia + acetazolamide. When ascending under control conditions a cascading decrease of arterial oxygen saturation (SaO2) has been observed probably because of the alternating dominance of peripheral and central mechanisms of ventilatory control. While the pre-treatment with intermittent hypoxia prolonged the constant SaO2 periods, the intake of acetazolamide eliminated this respiratory periodicity. Oxygen desaturation was best prevented by acetazolamide which was also associated with faster ascent times compared to control conditions.